Antiobesity and antihypercholesterolemic effects of white tea (Camellia sinensis) infusion on high-fat diet induced obese rats - Shiyan, Shaum; Herlina, Herlina; Bella, Annisa Mutiara (Universitas Ahmad Dahlan, 2017)
Obesity may cause the lipid metabolisms disorder so that a risk factor for hypercholesterolemic. Catechin and epigallocatechin gallate in white tea potentially inhibit lipase activity. Caffeine compounds and catechin derivatives have a role as antihypercholesterolemic. The objective of this study was to explore antiobesity and antihypercholesterolemic activity from white tea infusions to lipase and total cholesterol in rats model fed a high-fat-diet. Twenty-five rats were divided into five groups. Negative control group was administered with distilled water. The positive control group was administered with orlistat dose 14.2 mg/kgBW. Group 3rd, 4th, and 5th were treated with white tea infussion doses of 125, 250 and 500 mg/kgBW/day, respectivelly. period and feed intake was calculated daily during the treatment. White tea doses of 500 mg/kgBW decrease the total cholesterol by 37.16±11 mg/dL, lipase level of 23.70±0.64 U/L, weight up to 3.53±1.21 g/day and decrease feed intake by 12.71±1.76 g/day. The infusion of white tea can decrease total cholesterol level, lipase level, body weight and feed intake. This study concluded that infusion of white tea has antiobesity and antihypercholesterolemic effect on rats fed high-fat-diet.